The function of prohibitins in mitochondria and the clinical potentials - Linda Oyang; Jian Li; Xianjie Jiang; Jinguan Lin; Longzheng Xia; Lixia Yang; Shiming Tan; Nayiyuan Wu; Yaqian Han; Yiqing Yang; Xia Luo; Jinyun Li; et al. (Cancer Cell International, 2022)
Abstract Prohibitins (PHBs) are a class of highly evolutionarily conserved proteins that widely distribute in prokaryotes and eukaryotes. PHBs function in cell growth and proliferation or differentiation, regulating metabolism and signaling pathways. PHBs have different subcellular localization in eukaryotes, but they are mainly located in mitochondria. In the mitochondria, PHBs stabilize the structure of the mitochondrial membrane and regulate mitochondrial autophagy, mitochondrial dynamics, mitochondrial biogenesis and quality control, and mitochondrial unfolded protein response. PHBs has shown to be associated with many diseases, such as mitochondria diseases, cancers, infectious diseases, and so on. Some molecule targets of PHBs can interfere with the occurrence and development of diseases. Therefore, this review clarifies the functions of PHBs in mitochondria, and provides a summary of the potential values in clinics.